Analisis Konsep Produksi dalam Prespektif Syari’at Islam - Athaya Saputra, Deza; Nissa Najmi Fitri, Izzatun; Najmi Gunawan, Revaliana (Indonesia Economic Journal, 2025)
Production is a crucial element of economic activity that contributes to meeting human needs and improving social welfare. From an Islamic perspective, production activities are not merely considered an economic endeavor to achieve profit, but also a manifestation of worship and an expression of gratitude to Allah SWT for all the resources He has bestowed. Islam emphasizes that production activities must be based on moral principles such as integrity, justice, social responsibility, and sustainability. This distinguishes the Islamic concept of production from conventional production systems, which generally focus solely on profit. This research employs a library research method through an in-depth review of various literature, both classical and contemporary, that examines the principles of production within an Islamic economic framework. The research findings indicate that production in Islam aims to achieve harmony between worldly and hereafter interests through the lawful, efficient, and beneficial exploitation of resources. The primary goal of production is not merely the accumulation of material wealth, but also the realization of social welfare, equitable economic distribution, and the attainment of justice and blessings in every economic transaction. Thus, the concept of production from an Islamic perspective places moral and spiritual values ​​as the primary foundation of all economic processes, thus contributing to sustainable and equitable economic development.